Method for describing signal conversion processes in analog electronic systems - Mahmoud Al-Suod; Abdullah Eial Awwad; Alaa Al-Quteimat; Oleksandr Ushkarenko (Bulletin of Electrical Engineering and Informatics, 2022)
One of the main tasks of information technology is to improve existing and develop new methods for formal recording of various dynamic logical operations of analog and digital signal conversion in electronic control systems, acquisition, and processing of information. The stage of formal recording of any signal transformation process must be presented in the form of analytic symbols, the sequence of which must form a fully functional mathematical model. The improved method of the signals conversion processes description based on a representation of the mathematical models of the electronic circuits’ components in the grapho-analytical form with the increased information content allows integrating the developed models of electronic circuit elements with object-oriented programming language in the form of functional structures. It opens the way to perform parametric analysis of circuits and other tasks, related to the modeling of electronic systems.